Beginning with the Unlimited: Badiou and Plotinus on What Comes First - Ploug, Anna Cornelia (Res Cogitans, 2017)
The philosophical system of L'être et l'événement is launched with the explicit denial of ‘The One’ as grounding principle, because any philosophy that begins by positing an original unity (whether a unique, absolute being or an atom) will, according to Alain Badiou, inevitably turn out to be nothing but disguised theology. This denial, captured in the formula ”l'un, en effet, n'est pas" (Badiou 1988, 47), constitutes the precursory decision taken by Badiou in order to develop an ontological architecture, which permits pure multiplicity as its base. Who would be a more obvious counterpart for this announcement than Plotinus, the ultimate thinker of The One? While Badiou is not concerned specifically with reading or criticising neither Plotinus nor Neoplatonism as such, all the necessary aspects that he seeks to escape are present in the latter: The One of the Enneads is a transcendent unity, inaccessible to thought and beyond being. Badiou, on his part, insists that since The One is not, what originally is rather amounts to ‘inconsistent’ multiplicity, the pur multiple. Furthermore, he points to the process of ‘structuring situations’, i.e. arranging utter differentiation into consistent wholes, as the only place for unity: unity is nothing more than the operation of unifying, the compte-pour-un. However, I will argue that our understanding can benefit from subjecting certain schemes in the two authors to reconciliation instead of merely accepting the seeming antagonism. More specifically, I will show that there can be found a decisive resemblance in their perspectives on what comes first.